Tenurable Teaching-Focused Faculty Streams and Ranks in Canadian Universities: A Review of Collective Agreements - Potter, Tiffany; Symbaluk, Diane; Jackson, Brad; Andrews, David M. (Teaching and Learning Inquiry, 2025)
As in several other countries, Canada’s research-focused universities have seen an expansion in recent decades of tenurable or tenure-like teaching-focused faculty (TTFF) roles. TTFF streams are not new in Canada, but they have experienced growth in number and re-definition in scope at many universities. Despite its definitive impact in university/faculty relations, the language of negotiated collective agreements (contracts) has not been considered on a national scale. This study examined collective agreements in place on January 1, 2023, at 15 medical/doctoral and 15 comprehensive universities in Canada to determine whether they had TTFF positions. We investigated how these positions compared across institution types based on key features including definitions, duties, and workloads, promotion and tenure criteria, professional mobility and complement limits, sabbatical leave, and salary provisions. Findings indicate that TTFF streams were present in eight of the medical/doctoral universities and seven of the comprehensive universities. We conclude that tenurable or tenure-like teaching streams are no longer anomalous in Canada, and that while many universities construct these positions as teaching-only, TTFF contract language increasingly encompasses scholarly and curricular work outside the classroom with an identifiable impact on teaching and learning beyond one’s own students.